What Are Male and Female Students' Views of Science in a Society in Transition? A Self-Study of an Institution of Higher Education - Maura A. E. Pilotti; Khadija El Alaoui; Gaydaa Al-Zohbi (MDPI AG, 2022)
Consensus exists among countries of the world that science literacy is necessary for sustainability. Instruction may emphasize comprehension of scientific contents as well as the use of scientific information to examine and understand life on earth, but students' interest in science is the base on which such instruction rests. In the present field research, we examined female and male college students' views of science education within their chosen major (STEM versus non-STEM). We specifically selected students whose socio-cultural context is that of a society in transition from a patriarchal model to one that fosters gender equity. A successive-independent-samples design was used to administer a simplified version of the RISC surveys to two clusters of students differing in educational experience: entry-level students (first and second year) and exit-level students (third and fourth year). Female and male students majoring in STEM or non-STEM disciplines at each level were targeted. Although there were no gender differences in major selection at the entry level, at the exit level, male students were more numerous in STEM than non-STEM majors. Only a few gender differences were recorded in students' views of science education within their STEM and non-STEM majors. At the exit level, opinions about majors were positive across the board. In the microcosm of an academic institution inside a society once defined by patriarchy, gender is now less of a distinctive professional marker for students receiving a college education. Because attitudes are often linked to behavior, these findings also demonstrate the usefulness of periodic institutional assessments of not only students' performances but also attitudes and preferences to determine the need for gender equity interventions.